Phase-Stabilized Delivery for Multiple Local Oscillator Signals via Optical Fiber - Anxu Zhang; Yitang Dai; Feifei Yin; Tianpeng Ren; Kun Xu; Jianqiang Li; Jintong Lin; Geshi Tang (IEEE Photonics Journal, 2014)
In this paper, we propose and demonstrate a multiple local oscillator (LO) signal phase stabilization technique for long-distance fiber delivery. One of the LO signals, which acts as a reference single, is round-trip transferred between the central station and the remote end, carrying the phase variation arises from perturbations of the fiber link. The wavelength of the optical carrier is adjusted according to the phase variation of the reference LO, to stabilize the delay of the fiber link. Once the delay of the link is stabilized, the phases of other LO signals that transferred through the same fiber link will all be stabilized. Meanwhile, the delay tunable range is in proportion to the fiber length, which means a very long delivery distance can be expected. Experimentally, LOs at frequencies of 2.46 GHz and 8 GHz are transferred through a 30-km fiber link, and significant phase drift compression is observed at both frequencies.